The Influence of Paylater Existence on the Level of Impulsive Buying Behavior in Society - M Gelar Faisal (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to examine the influence of PayLater's existence on the level of impulsive buying behavior in society. The method used involves in-depth analysis, incorporating observation and literature review to assess impulsive buying behavior and the use of PayLater services. The results indicate that the dependent variable, PayLater’s existence, can be explained by the independent variable, which is the level of impulsive buying behavior in society, while the remainder is explained by other factors. The study concludes that the PayLater system facilitates immediate product purchases, with payment made in installments. Impulsive buying behavior is most prevalent among individuals aged 18-21 years. The PayLater system has both positive and negative implications: on the positive side, it enables users to acquire essential products during urgent financial needs; however, it also fosters consumerism and may encourage impulsive purchases.